2009
DOI: 10.2215/cjn.00810208
|View full text |Cite
|
Sign up to set email alerts
|

Mild Fetal Renal Pelvis Dilatation—Much Ado About Nothing?

Abstract: Background: Renal pelvis dilatation (RPD) occurs in 1% of fetuses. Severe RPD (>15 mm) is frequently associated with urinary tract pathology. For the majority with mild (5 to 9 mm) to moderate (10 to 15 mm) RPD, however, there is uncertainty about the risk of abnormalities and how much postnatal investigation is required.Study design: Systematic review of cohort studies of fetuses with RPD < 15 mm and metaregression to estimate risks of postnatal RPD, obstruction, and VUR.Results: Of 506 potentially relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 51 publications
(80 reference statements)
4
21
0
2
Order By: Relevance
“…By adopting this criterion, the chance of identifying an infant without any congenital anomaly of the urinary tract increased five times compared with the first period of our study. Of note, recently, Hothi et al (28) performed a systematic review of cohort studies of fetuses with RPD,15 mm. The work by Hothi et al (28) showed that the estimated risks of obstruction and VUR were quite low, particularly in the mild group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By adopting this criterion, the chance of identifying an infant without any congenital anomaly of the urinary tract increased five times compared with the first period of our study. Of note, recently, Hothi et al (28) performed a systematic review of cohort studies of fetuses with RPD,15 mm. The work by Hothi et al (28) showed that the estimated risks of obstruction and VUR were quite low, particularly in the mild group.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recently, Hothi et al (28) performed a systematic review of cohort studies of fetuses with RPD,15 mm. The work by Hothi et al (28) showed that the estimated risks of obstruction and VUR were quite low, particularly in the mild group. Therefore, there are still many controversies regarding the clinical significance of mild isolated ANH.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital abnormalities of the kidney and urinary tract comprises a broad spectrum of anatomical defects that range from asymptomatic abnormalities to lethal conditions [26][27][28][29]. It has been estimated that CAKUT occurs at a frequency of 1 in 500 live births [7,30].…”
Section: Discussionmentioning
confidence: 99%
“…Renal pelvic dilation (RPD) is the most common organspecific fetal condition detected during the antenatal period and one of the most difficult diagnostic challenges [1][2][3][4][5]. An increasing number of renal anomalies are identified prenatally in otherwise uncomplicated pregnancies.…”
Section: Introductionmentioning
confidence: 99%